Horizontal gene transfer of epigenetic machinery and evolution of parasitism in the malaria parasite Plasmodium falciparum and other apicomplexans - Kishore, Sandeep P.; Stiller, John W.; Deitsch, Kirk W. (My University, 2013)
The acquisition of complex transcriptional regulatory abilities and epigenetic machinery facilitated the transition of the ancestor of apicomplexans from a free-living organism to an obligate parasite. The ability to control sophisticated gene expression patterns enabled these ancient organisms to evolve several differentiated forms, invade multiple hosts and evade host immunity. How these abilities were acquired remains an outstanding question in protistan biology. In this work, we study SET domain bearing genes that are implicated in mediating immune evasion, invasion and cytoadhesion pathways of modern apicomplexans, including malaria parasites. We provide the first conclusive evidence of a horizontal gene transfer of a Histone H4 Lysine 20 (H4K20) modifier, Set8, from an animal host to the ancestor of apicomplexans. Set8 is known to contribute to the coordinated expression of genes involved in immune evasion in modern apicomplexans. We also show the likely transfer of a H3K36 methyltransferase (Ashr3 from plants), possibly derived from algal endosymbionts. These transfers appear to date to the transition from free-living organisms to parasitism and coincide with the proposed horizontal acquisition of cytoadhesion domains, the O-glycosyltransferase that modifies these domains, and the primary family of transcription factors found in apicomplexan parasites. Notably, phylogenetic support for these conclusions is robust and the genes clearly are dissimilar to SET sequences found in the closely related parasite Perkinsus marinus, and in ciliates, the nearest free-living organisms with complete genome sequences available. Animal and plant sources of epigenetic machinery provide new insights into the evolution of parasitism in apicomplexans. Along with the horizontal transfer of cytoadhesive domains, O-linked glycosylation and key transcription factors, the acquisition of SET domain methyltransferases marks a key transitional event in the evolution to parasitism in this important protozoan lineage.